“Chacco” clay from the Peruvian highlands as a potential adsorbent of heavy metals in water - Gonzales-Condori, Elvis G. (2024)
This research aimed to remove Cd (II), Cr (VI), Ni (II), Pb (II), and V (V) from aqueous solutions prepared in distilled water using “Chacco” clay from the Peruvian highlands as adsorbent. The adsorption process was carried out in Batch type systems for 120 min using solutions of each metal at a concentration of 5 mg/L in aqueous systems of a single metal or monometallic (MAS) and solutions of the five metals simultaneously or multimetallic (MMAS). For this purpose, the “Chacco” clay was first characterized by SEM-EDS analysis, finding a laminated clay structure with an elemental composition of C, Al, Fe, Na, Mg, Ca, K, As, Cu, Pd, O, and Ta. The results using 10 g/L of “Chacco” clay showed that the best adsorption efficiency in both MAS and MMAS aqueous systems is achieved at pH = 4 achieving in MAS aqueous systems the removal of 64.16 ± 0.98 % of Cd (II), 95.70 ± 0.81 % of Cr (VI), 97.20 ± 0.89 % of Ni (II), 92. 78 ± 0.79 % of Pb (II), and 95.80 ± 0.67 % of V (V), on the other hand, in aqueous MMAS systems a decrease in adsorption efficiency was observed, managing to remove 6.88 ± 0.53 % of Cd (II), 63.04 ± 0.94 of Cr (VI), 7.81 ± 0.43 % of Ni (II), 62.34 ± 0.77 % Pb (II), and 14.33 ± 0.56 % of V (V). The kinetic study showed that the adsorption mechanism would correspond to chemisorption since the process fitted best to the pseudo-second order model and Elovich. SEM-EDS analysis after adsorption confirmed the presence of the heavy metals under study in the “Chacco” clay. Metal adsorption is evidenced at 1418 cm− 1 by -CH2-metal deformation vibrations according to FTIR analysis. In conclusion, the “Chacco” clay would be a promising adsorbent of heavy metals in polluted waters so that scaling up to real environments could be feasible. On the other hand, the “Chacco” clay is consumed by the population of Puno, Peru, therefore its potential impact on health should be evaluated due to its capacity to accumulate metals and the presence of Al in this clay.